Contrasting results of tests of peripheral vestibular function in patients with bilateral large vestibular aqueduct syndrome. Issue 8 (August 2017) - Zhou, Yu-Juan; Wu, Yong-Zhen; Cong, Ning; Yu, Jing; Gu, Jun; Wang, Jing; Chi, Fang-Lu
Highlights: LVAS patients have lower VEMP thresholds, higher amplitudes, and shorter latencies. The otolithic organs in patients with LVAS are hypersensitive to sound or pressure. Patients with LVAS have semicircular canal hypofunction and disequilibrium. Abstract: Objective: To analyze and summarize the effect of bilateral large vestibular aqueducts in peripheral vestibular organ function. Methods: Eighteen patients with bilateral large vestibular aqueduct syndrome (LVAS; Study Group) and 18 healthy volunteers (Control Group) were investigated using audiometry, caloric test, sensory organization test (SOT), and vestibular-evoked myogenic potential (VEMP) tests. Results: All 18 patients (36 ears) exhibited sensorineural hearing loss. For cervical VEMP (cVEMP), the Study Group showed lower thresholds (Study Group vs. Control Group: 71.4 vs. 75.3 dB nHL; p  = 0.006), N1 latencies (24.1 vs. 25.2 ms; p  = 0.026) and shorter P1 (15.3 vs. 16.6 ms; p  = 0.003), and higher amplitudes (400.7 vs. 247.2 µV; p  < 0.001) than the Control Group. For ocular VEMP (oVEMP), the Study Group had lower thresholds (79.3 vs. 81.8 dB nHL; p  = 0.046) and higher amplitudes (40.6 vs. 14.4 µV; p  < 0.001) than the Control Group. Fourteen of 16 patients (87.5%) who completed caloric tests had abnormal results, and 10 of 18 patients (55.6%) exhibited abnormal results in SOTs. Conclusions: The hyperfunction of vestibular test in otolithic organs and the hypofunction of vestibular test in semicircular canals, as well as the dysfunction in the balance test were demonstrated in patients with LVAS. Significance: Our findings can help clinicians gain a better understanding of the characteristics of vestibular organ function in patients with LVAS, which can facilitate optimal targeted treatment.